(untitled) (Global Journal of Science Frontier Research, 2019)
One of the most crucial and substantial factor in any of the crop for its triumph, seedling quality remains the foremost position which can be enhanced by its density resulting in the robustness, ultimately increasing the overall performance of vegetable crop. Nevertheless, their densities give rise to the vigor one influencing their survival and early establishment, being the major consideration affecting the growth and health of seedling further influencing the crop productivity. Therefore, an experiment was carried out to identify the optimum seedling density and study their effect on different morphological attributes of Broccoli cv. Green Pia, Cabbage var. Green Top and Cauliflower var. Snow Mystique in both lab and field conditions. The research design was Randomized Complete Block Design with four treatments viz. 0.5cm × 1.0cm (T1), 1.0cm × 1.0cm (T2), 1.5cm × 1.5cm (T3), and 2.0cm × 2.0cm (T4) replicated five times. Destructive sampling was done after 23 days of seed sowing to study the growth attributes viz. plant height, number of leaf, leaf area, root length, root fresh weight, shoot fresh weight, shoot dry weight and dry weight percentage. Software image J was used to measure leaf area, MS-Excel for data tabulation which were analyzed by using GenStat 15 th Ed. Germination percentage was 84%, 86%, 88.0% in lab while seedling establishment was 53%, 66.3%, 70.3% in nursery bed respectively for Cabbage, Cauliflower and Broccoli.